Knitted Ti₃C₂Tₓ MXene based fiber strain sensor for human-computer interaction - Fu, Xiyao (2022)
Fiber-based stretchable electronics with feasibility of weaving into textiles and advantages of light-weight, long-term stability, conformability and easy integration are highly desirable for wearable electronics to realize personalized medicine, artificial intelligence and human health monitoring. Herein, a fiber strain sensor is developed based on the Ti3C2Tx MXene wrapped by poly(vinylidenefluoride-co-trifluoroethylene) (P(VDF-TrFE)) polymer nanofibers prepared via electrostatic spinning. Owing to the good conductivity of Ti3C2Tx and unique 3D reticular structure with wave shape, the resistance of Ti3C2Tx@P(VDF-TrFE) polymer nanofibers changes under external force, thus providing remarkable strain inducted sensing performance. As-fabricated sensor exhibits high gauge factor (GF) of 108.8 in range of 45-66% strain, rapid response of 19 ms, and outstanding durability over 1600 stretching/releasing cycles. The strain sensor is able to monitor vigorous human motions (finger or wrist bending) and subtle physiological signals (blinking, pulse or voice recognition) in real-time. Moreover, a data glove is designed to connect different gestures and expressions to form an intelligent gesture-expression control system, further confirming the practicability of our Ti3C2Tx@P(VDF-TrFE) strain sensors in multifunctional wearable electronic devices.